New Parametrizations for a Model with Nonlinear Derivative Couplings - 陈晏军 (Chinese physics letters, 2014)
We propose three parameter sets for the Lagrangian with nonlinear derivative couplings in the relativistic mean field theory. The properties of finite nuclei and nuclear matter are explored. The study shows that a good description of binding energies, charge radii and neutron skin thickness of nuclei is achieved with this Lagrangian. It is also shown that this Lagrangian model leads to a softening of the equation of state and symmetry energy at high densities, and gives a much less repulsive optical potential at high nucleon energies compared to standard relativistic mean field models.